2021
DOI: 10.1038/s41598-021-86114-4
|View full text |Cite
|
Sign up to set email alerts
|

Predicting amyloid positivity in patients with mild cognitive impairment using a radiomics approach

Abstract: Predicting amyloid positivity in patients with mild cognitive impairment (MCI) is crucial. In the present study, we predicted amyloid positivity with structural MRI using a radiomics approach. From MR images (including T1, T2 FLAIR, and DTI sequences) of 440 MCI patients, we extracted radiomics features composed of histogram and texture features. These features were used alone or in combination with baseline non-imaging predictors such as age, sex, and ApoE genotype to predict amyloid positivity. We used a reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 67 publications
1
50
0
Order By: Relevance
“…Apart from the classification task, radiomics could display unique advantages in the field of frontotemporal dementia. Radiomics features have, in fact, demonstrated an optimal predictive power in terms of response to therapy or clinical outcomes in the field of oncology and neurodegeneration ( Feng and Ding, 2020 ; Conti et al, 2021 ; Kim et al, 2021 ). Hence, radiomics, even in combination with non-imaging data such as clinical scales and biological markers, might reasonably be used to enhance the predictive potential of medical imaging in FTD subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the classification task, radiomics could display unique advantages in the field of frontotemporal dementia. Radiomics features have, in fact, demonstrated an optimal predictive power in terms of response to therapy or clinical outcomes in the field of oncology and neurodegeneration ( Feng and Ding, 2020 ; Conti et al, 2021 ; Kim et al, 2021 ). Hence, radiomics, even in combination with non-imaging data such as clinical scales and biological markers, might reasonably be used to enhance the predictive potential of medical imaging in FTD subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested neuroimaging modalities as good predictors for Aβ+ status. One group proposed the least absolute shrinkage selection (LASSO) regression method to predict Aβ+ in 440 aMCI subjects [28]. Radiomics features were extracted from MRI images with hippocampus and precuneus as regions of interest (ROIs) and were used alone or in combination with baseline non-imaging predictors.…”
Section: Protein Biomarkers For Admentioning
confidence: 99%
“…By themselves, amyloid biomarkers are insufficient in monitoring the progression of AD after symptom onset [7]. N-status can be assessed via brain magnetic resonance imaging (MRI) or brain 18 F-FDG-PET. Besides its utility in the diagnostic process of AD, 18 F-FDG-PET has proven utility in disentangling several phenotypes of dementia and cognitive decline [8,9].…”
Section: Introductionmentioning
confidence: 99%